Creativity : a short and cheerful guide - Cleese, John (Crown, 2020)
The Monty Python comic master shares lighthearted advice on how anyone can learn the skill of creativity, drawing on personal experience to explain how to get into the right frame of mind, develop worthwhile ideas, and overcome blocks.